Communicative paradigm or cultural research - M. I. Boychenko, (Ukrainian Cultural Studies, 2018)
In the article the culture is considered from the perspective of the priority of its communicative dimension. Social communication emerges as the basis for the creation and reproduction of culture as one of the important means and to some extent the ultimate goal of cultural development. The grounded thesis is that satisfactory consideration of the functioning of culture in a society is impossible without taking into account communicative mechanisms of its provision. It reveals the leading role of values in determining the communication as a functional basis of culture: the values of culture, acquiring functional social purpose (in particular, in the form of social roles), ensure the participation of society members in both social life in general and in its development by means of culture. The communicative criterion makes possible to define as culture only that things made by a person, which promote social communication, that is, that ensure the reproduction and development of society. In addition, social communication is not only a means and a criterion for the development of culture, but also should be considered as a goal of its development – both in the obvious case of communicative culture and in the broader sense of the culture of any communication. In the first, narrow sense we are talking about is close in importance to etiquette. In the second, broad sense which sets the value-semantic horizon for understanding the culture in general, the latter appears as a communication – actual and potential. To determine the systemic dimensions of the culture functioning one should determine the levels of implementation of social communication in society. After all, culture is the product of human communication, and it is also the cause and the foundation - even when it comes to personal culture (since everything done by a person needs to be checked and reinforced or denied by others). In general, it is worth to think about building acommunicative concept of culture, which would proceed from the idea of an intersubjective essence of a human as a social being. The following levels should be distinguished, from the lowest to the highest: direct interaction, interaction within organizations and communities, cooperation within countries as complex territorial associations of communities, interaction within the framework of a global society as a super-"community". At each of these levels, there are varieties of values that attract individuals to engage in communication at the appropriate level. In turn, these values determine certain social roles and functional queries that are distributed or grouped around these social roles. The fulfillment of social roles forms the basis of the culture of social communication, that is more or less developed. Performing roles is concentrated in the personal culture of communication only at first glance - both skill and persuasiveness and successful performance. In addition to the personal culture of communication participation, the collective communication culture should be distinguished, most of which consists in those unwritten rules of conduct that, without special arrangements and even without articulation, are implicit, but certainly perceived by the communicative community as the basis for a successful social life. The higher the level of social communication, the greater the success of social interaction depends on the reinforcement of unwritten rules of conduct rationalized norms. Universalist norms represent the means of guaranteeing mutual understanding at the highest levels of social communication. In order to treat culture as a certain ideal and as the embodiment of higher values, which we can and should endlessly seek and approach, we must first (in the mode of pre-understanding) comprehend culture as the external side of our experience, as that which in general enables any our act and aspiration. Such an interconnection of the beginning and end, goals and means can be gained through the study of social communication – and at each of the aforementioned level, this connection is specific. However, each time it is a connection between certain values that define the goals, and certain functions that determine the means of communication. We should strive to establish the definition of the concept of values interconnected with the definition of the culture notion. Valuable analysis of this is, at the same time, an analysis of values as a subject of research, and an analysis from the standpoint of values, that is, values should serve as the basis of our methodology. Since it is a question of human knowledge of human activity, there is no contradiction here, but there is a performative statement of the methodology of the study, its formation under the influence of an even deeper immersion in the subject of knowledge. This means that the methodology should come from our way of life, and not be reaffirmed by the backwards of some forced indents and compromises with our way of life.
Keywords: culture, communication, social communication, values, social functions, social roles, social technology